M-learning App: Learning and Understanding Through Visuals (Heredity & Variation) - Lokman, Anies Adielah; Wan Ismail, Wan Shazlina (Journal of Computing Technologies and Creative Content, 2020)
Mobile penetration among teenagers aged 15 years and above has spiraled to 70% on 2017. This has paved the way for educational system to technologically step up. M-learning is defined by how mobile devices are used as a learning tool in education. The aim of this research is to develop an M-learning application for Science Subject Form 4 Chapter 3 as another medium for students to master a chapter in short period of time. This research also focuses on improvising user interface (UI) and enhancing user experience (UX). This research will also evaluate the effectiveness of mobile learning apps as a learning medium among Form 4 students.